Verbal autopsy: an analysis of the common causes of childhood death in the Barekese sub-district of Ghana - Stephen Manortey; Adrienne Carey; Daniel Ansong; Ryan Harvey; Brian Good; Joseph Boaheng; Benjamin Crookston; Ty Dickerson (AOSIS, 2011)
The availability of mortality data for any society plays an essential role in health monitoring and evaluation, as well as in the design of health interventions. However, most resource-poor countries such as Ghana have no reliable vital registration system. In these instances, verbal autopsy (VA) may be used as an alternative method to gather mortality data. In rural Ghana, the research team utilized a VA questionnaire to interview caretakers who were present with a child under the age of five prior to death. The data was given to two physicians who independently assigned the most probable cause of death for the child. A third, blinded physician analyzed the data in the cases where the first two physicians disagreed. When there was agreement between physicians, this was assigned as the cause of death for the individual child. During the study period, we recorded 118 deaths from 92 households. Twenty-nine (24.6%) were neonatal deaths with the leading causes of death being neonatal sepsis, birth asphyxia and pneumonia. The remaining 89 (75.4%) were post-neonatal deaths with the most common causes of death being pneumonia, malaria and malnutrition. While 63/118 (53.4%) deaths occurred in the home, there is no statistically significant relationship between the location of the home and the time of travel to the nearest health facility (P=0.132). VA is an important epidemiological tool for obtaining mortality data in communities that lack reliable vital registration systems. Improvement in health care is necessary to address the large number of deaths occurring in the home.